The Effectiveness of Painting Therapy in Improving Attention Deficit Hyperactivity Disorder, and Separation Anxiety in Female Second-Grade Students - Gholabedini, Fatemeh; Sabori, Hamed (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Attention deficit hyperactivity disorder (ADHD) is a developmental neurological disorder and a common childhood disorder that has attracted the attention of psychologists, psychiatrists, and clinical specialists; hence, the present study aimed to determine the effectiveness of painting therapy on attention deficit hyperactivity disorder, and separation anxiety in second-grade female students at primary schools of Bastak County in the school year 2020-2021. Methods: The study had a quasi-experimental design with pretest-posttest and a control group. The statistical population of the study consisted of all female second-grade students of Bastak primary schools in the school year 2020-2021. The sample group was selected by the convenience sampling method and divided into two experimental (n=20) and control (n=20) groups using random assignment. The Child Symptom Inventory-4 (CSI-4) was used to collect data. After performing the pre-test, the experimental group received painting therapy for ten 90-minute sessions, but the control group did not receive any intervention. After collecting pre-test and post-test, the data were analyzed using the statistical method of analysis of covariance (ANCOVA) and statistical software (SPSS). Results: The results of analysis of covariance indicated that there was a significant difference between attention deficit hyperactivity disorder and separation anxiety in the control and experimental groups in the post-test after eliminating the pre-test effect, and painting therapy had a significant effect on attention deficit hyperactivity disorder and separation anxiety in female second-grade students. Conclusion: Therefore, the results of painting therapy can be used as a useful non-pharmacological therapy in clinical situations and the treatment of separation anxiety problems in children.